Keefektifan Penggunaan Strategi Think-Pair-ShareMata Pelajaran Ilmu Pengetahuan Sosial (IPS) Sub-Sub Tema Keadaan Iklim Indonesia Kelas VIIMadrasah Tsanawiyah Negeri Surakarta 1Tahun Ajaran 2015/2016 - Septikasari, Erwin; , Drs. Suharjo, M.S (2016)
MTs Land of Surakarta 1 are on the MT. Haryono 24D Sidorejo village, Mangkubumen, Banjarsari, Surkarta. The use of learning strategy is needed to make the state of class become more active and the student do not feel bored in learning so that student would be more active and result of learning and teaching also in accordance with the desired. The purpose of this research namely to know the strategy effectivenes of the use of Think Pair Share on the state of Indonesia class climate VII public MTs Surakarta 1. Research method used is experiment with a population of public MTs student Surakarta 1 with sample VII PK1 class and VII PK3. Class experiment in the process of learning and teaching use strategy Think Pair Share on class VII PK1, while class control use strategy jigsaw on class VII PK3. The result of this research can be concluded that the use of strategy Think Pair Share with matter the state of climate Indonesia class VII MTs land Surakarta 1 show an increase the average score student learning process of 7,97 from the result of the average score pretest 64,32 and on the value posttest increased be 72,29. Based on the result of the independent sample test obtained value significant 0,000 < 0,05 means Ho rejected. The results of the analysis can be seen that there is an increase the success of study use strategy Think Pair Share in sub the theme the state of climate Indonesia social class integrated class VII public MTs Surakarta 1 academic year 2015/2016.